A comparative evaluation of bioequivalence of Gan & Lee glargine U300 and Toujeo® in Chinese healthy male participants - Li, Xiaoli; He, Anshun; Liu, Bingyan; Shan, Rongfang; Zhu, Juan; Li, Xiaoyue; Xie, Tian; Li, Yue; Chen, Mengmeng; Su, He; Zhang, Chaoyang; Li, Lufeng; et al. (Frontiers in Endocrinology, 2024)
Background: To assess the bioequivalence between Gan & Lee (GL) glargine U300 and Toujeo ® regarding pharmacokinetics (PK), pharmacodynamics (PD), and safety in Chinese healthy male participants.Methods: A single-center, randomized, double-blind, single-dose, two-preparation, two-sequence, four-cycle repeated crossover design study was performed to compare GL glargine U300 and Toujeo ® in 40 healthy participants. The primary PK endpoints were the area under the curve of glargine metabolites, M1 concentration from 0 to 24 hours (AUC0-24h), and the maximum glargine concentration within 24 hours post-dose (Cmax). The primary PD endpoints were the area under the glucose infusion rate (GIR) curve from 0 to 24 hours (AUCGIR.0-24h) and the maximum GIR within 24 hours post-dose (GIRmax).Results: GL Glargine U300 demonstrated comparable PK parameters (AUC0-24h, Cmax, AUC0-12h, and AUC12-24h of M1) and PD responses [AUCGIR.0-24h, GIRmax, AUCGIR.0-12h, and AUCGIR.12-24h] to those of Toujeo ® , as indicated by 90% confidence intervals ranging from 80% to 125%. No significant disparities in safety profiles were observed between the two treatment groups, and there were no reported instances of serious adverse events.The PK, PD, and safety of GL glargine U300 were bioequivalent to that of Toujeo ® .